The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.ypmed.2015.12.012
|View full text |Cite
|
Sign up to set email alerts
|

A community based primary prevention programme for type 2 diabetes integrating identification and lifestyle intervention for prevention: the Let's Prevent Diabetes cluster randomised controlled trial

Abstract: Aims: Prevention of type 2 diabetes (T2DM) is a priority in healthcare, but there is a lack of evidence investigating how to effectively translate prevention research into a UK primary care setting. We assessed whether a structured education programme targeting lifestyle and behaviour change was effective at preventing progression to T2DM in people with prediabetes.. Materials and methods:44 General Practices were randomised to receive either standard care or a six hour group structured education programme wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 27 publications
2
92
0
Order By: Relevance
“…We have not systematically searched for more recent primary studies not included in the reviews considered here. However, the latest update from the DPP is in keeping with the results reviewed,43 as are the results of additional recent trials,44 45 including trials based in routine practice, where clinical benefits were found to be modest 4647 We excluded non-English language publications that we were unable to access (see figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…We have not systematically searched for more recent primary studies not included in the reviews considered here. However, the latest update from the DPP is in keeping with the results reviewed,43 as are the results of additional recent trials,44 45 including trials based in routine practice, where clinical benefits were found to be modest 4647 We excluded non-English language publications that we were unable to access (see figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Eight hundred and eighty patients were enrolled in the cluster RCT from July 2009 to June 2011, with 447 patients (51%) in the intervention group and 433 (49%) in the standard care group 10. Those randomised to standard care received a booklet giving information on risk factors for T2DM and how physical activity and lifestyle change can be used to prevent or delay the disease.…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome of the Let's Prevent Diabetes randomised controlled trial (RCT) was progression to T2DM during 3 years. Overall, there was a non-significant 26% reduction in the risk of developing T2DM in the intervention arm compared with standard care (p=0.18) 10. A significant reduction in progression to T2DM was seen in the intervention arm compared with standard care when only those who attended all of the education sessions (ie, the initial 6 hours plus the two annual refresher sessions) were included in the analysis (LJ Gray, T Yates, J Troughton, et al .…”
Section: Introductionmentioning
confidence: 99%
“…A recent large-scale randomised controlled trial to evaluate the effect of a type 2 diabetes prevention lifestyle intervention (Let's Prevent) in a UK community setting failed to show a statistically significant reduction in progression to type 2 diabetes at 3 years compared with normal care, 9 that is, it failed to do the thing that it was supposed to do. Retrospective re-analysis of the data did show a significant reduction in progression to diabetes in the subgroup of patients who engaged and then attended subsequent sessions, with the greatest benefit seen for the 29.1% of patients randomised to the intervention who attended all sessions.…”
Section: Diabetes Prevention Programmesmentioning
confidence: 99%